A Novel Inverter Topology for Single-Phase Transformerless PV System - Haiyan Cao (Active and Passive Electronic Components)
Transformerless photovoltaic (PV) power system is very promising due to its low cost, small size, and high efficiency. One of its most important issues is how to prevent the common mode leakage current. In order to solve the problem, a new inverter is proposed in this paper. The system common mode model is established, and the four operation modes of the inverter are analyzed. It reveals that the common mode voltage can be kept constant, and consequently the leakage current can be suppressed. Finally, the experimental tests are conducted. The experimental results verify the effectiveness of the proposed solution.